FACTORS AFFECTING QUALITY OF PROFIT IN MANUFACTURING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Simamora, Katrin (International Journal of Public Budgeting, Accounting and Finance, 2020)
The purpose of this study is to find out and analyze the factors that influence earnings quality in manufacturing companies listed on the Indonesia Stock Exchange. The dependent variable in this study is Profit Quality. Capital Structure, Liquidity, Sales Volatility and Operating Cycles as independent variables and company size as moderating variables. The object of this research is manufacturing companies listed on the Indonesia Stock Exchange in 2015-2018. The sampling technique uses purposive sampling method. The research sample consisted of 72 companies with 288 units of observation. Data analysis method is secondary data using Eviews 9. The results of this study indicate that capital and liquidity structures have a positive and significant effect on earnings quality. Sales volatility and operating cycles have a negative and significant effect on earnings quality. Company size variable is able to moderate the effect of capital structure and operating cycle on earnings quality while company size is not able to moderate the effect of liquidity and sales volatility.